Glucosinolates are produced in trichomes of Arabidopsis thaliana - Frerigmann, Henning; Böttcher, Christoph; Baatout, Dunja; Gigolashvili, Tamara (Frontiers in Plant Science, 2012)
Glucosinolates (GS) are important plant secondary metabolites in plant resistance to herbivores, bacteria, and fungi, which have been shown to be accumulating in different organs and tissue types at varying concentrations. There are more than 200 GS species found in order Brassicales and presence of these compounds is well documented on organ-specific but not on cell-specific level. We used UPLC/ESI-QTOF-MS to measure the presence of GS and qRT-PCR to analyse the expression of GS biosynthetic and regulatory genes in isolated Arabidopsis thaliana trichomes. Trichomes of Arabidopsis are shown to synthesize chemoprotective aliphatic glucosinolates (AGS) and indolic glucosinolates (IGS), which are known for their biological activities against fungi, bacterial pathogens, or herbivores. UPLC/ESI-QTOF-MS analysis of various IGS mutants reveal increased or decreased levels of IGS in trichomes of gain- and loss-of-function mutants correspondingly. Using pMYB51/HIG1-uidA and pMYB28/PMG1/HAG1-uidA reporter plants we demonstrate that production of these important compounds is activated in trichomes of leaves or inflorescences in response to wounding. Since trichomes represent the first interface in plant-environment interactions, the possible role of GS containing trichomes in plant defense or signaling is discussed.